PENYULUHAN FAKTOR RISIKO PENYAKIT KARDIOVASKULER (PKV) DAN PEMERIKSAAN KADAR KOLESTEROL PADA GURU SD DI KECAMATAN SUKAWATI GIANYAR - I Gusti Agung Dewi Sarihati; Cok Dewi Widhya HS; I Gusti Ayu Sri Dhyanaputri; Heri Setiyo Bekti; Ida Bagus Oka Suyasa (Poltekkes Kemenkes Denpasar, 2020)
ABSTRACTHigh cholesterol increases the likelihood of the deposition of excess cholesterol in the walls of blood vessels and forming plaque, resulting in narrowing of the lumen and if left untreated can clog arteries and lead to cardiovascular disease. To prevent this, it can be done following a healthy lifestyle as endeavored by the Ministry of Health of the Republic of Indonesia. This community service aims to increase public knowledge and provide cholesterol check services in the prevention of cardiovascular disease that is carried out in Sukawati I District, Gianyar. The results showed that before counseling 5.4% of respondents answered 75% or more of the questions correctly. After being given an explanation accompanied by a leaflet, the respondent's knowledge became marked by an increase in the ability to answer that is 97.3% able to answer questions above 75%. Respodents with cholesterol levels above normal are most often found in respondents who have less knowledge that is 50%, the rest are found in respondents with sufficient and good knowledge. Percentage of respondents with normal cholesterol levels is most often found in respondents who have sufficient knowledge that is 74%. From these data it can be concluded that the total cholesterol level of respondents above normal is most often found in respondents with less knowledge. Thus, it is necessary to do continuous counseling to be able to change behavior towards supporting the prevention of cardiovascular disease.